Performances Of Tropical Holstein Friesian (Bos Taurus) X Thrabam (Bos Indicus) F1 Daughters Managed Under Bhutanese Farming Environment (SAARC Journal of Agriculture, 2024)
Local Thrabam cattle were inseminated with semen of four sire-lines of Tropical Holstein Friesian (THF) at selected sites of three agro-ecological zones of Bhutan. To understand their performances, progeny born from each sire-line were recorded and milk yield of F1 daughters were measured. Management practices were observed through farm visits. Result indicated that insemination in natural heat produced significantly higher calves than in induced heat (p